Evaluation of Prevalence of Medication Errors in a Multispecialty Teaching Hospital, Dehradun (Uttarakhand), India - B, Rekha; B, Saurabh (Indian Journal of Pharmacy Practice)
Background: Medication error is recognized as the eighth leading cause of death. Objective: The study was proposed to evaluate the prevalence and types of medication errors in IPD (In-patient department) at multispecialty teaching hospital of Dehradun (Uttarakhand). Materials and method: This cross sectional and prospective study was carried out on 250 patients admitted in different wards of hospital. Result: The results of the present study revealed that among the prescribing errors, complete instructions to the patients regarding the use and side effects of drugs were not mentioned in any prescription (100%). Other major prescribing errors were absence of weight of patients (100%), registration number of prescribers (100%), allergic specification (100%), poor handwriting (74.4%) and use of abbreviations (100%). Maximum errors while dispensing were, failure to educate the patient regarding the use of medication (90%) followed by substitution and short supply of medicines (48%). Maximum causes of errors as perceived by interviewing the nurses were when they are distracted by other patients, coworkers or events on the unit (74%) followed by confusion between two drugs with similar names (72%). Conclusion: Medication error can occur anywhere in the healthcare system from prescriber to dispenser to administrator and finally to patients use. Thus reporting and prevention of medication error has become an important part because therapeutic outcome of drug therapy increase with reduction of medication error incidences which will, ultimately improve the quality of patient's life.
Keywords: Medication errors; Prescription; Dispensing